How Teachers Enact Differentiated Learning Evaluation: Pedagogical Competence in a Merdeka Curriculum Pioneer School - Dewi Marya Susanti; Harjito Harjito; Maryanto Maryanto (Papanda Publisher, 2026)
This study examined how teachers at SD Negeri 3 Krangganharjo, a Pioneer School implementing the Merdeka Curriculum in Grobogan Regency, enact pedagogical competence in differentiated learning evaluation. A descriptive qualitative design was employed, with data collected over five months (June–November 2025) through semi-structured interviews, passive participatory classroom observation, and document analysis. Participants comprised the school principal, classroom teachers of Grades IV–VI, and students from the same levels. Instrument validity was established through expert content review, and intercoder reliability yielded κ = 0.82. Data analysis followed Miles and Huberman's interactive model; trustworthiness was ensured via source, technique, and time triangulation. Four interrelated findings emerged: (1) teachers deployed varied product-based assessment formats aligned with students' strengths and preferences; (2) task complexity was tiered according to readiness profiles; (3) evaluation was embedded continuously within instruction rather than confined to summative endpoints; and (4) individualized, growth-oriented feedback was consistently provided. An unexpected finding revealed that students demonstrated metacognitive awareness of differentiated evaluation as equitable rather than discriminatory. These practices reflect an enabling institutional culture in which evaluation autonomy, bounded by learning objectives, supports student-centered, inclusive assessment. The study contributes an empirically grounded framework for understanding differentiated evaluation competence within Merdeka Curriculum implementation.